2021
DOI: 10.1016/j.jmh.2021.100035
|View full text |Cite
|
Sign up to set email alerts
|

The systemized exploitation of temporary migrant agricultural workers in Canada: Exacerbation of health vulnerabilities during the COVID-19 pandemic and recommendations for the future

Abstract: In 2018, 55,734 jobs in Canadian agriculture were filled by temporary migrant workers, accounting for nearly 20 percent of total employment in this sector. Though referred to as temporary, those migrant workers often fill long-term positions and provide crucial support to the Canadian agricultural industry, which has seen an increasing disengagement from the domestic workforce in the last fifteen years. Health vulnerabilities faced by temporary migrant workers are already well documented. In addition, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 6 publications
0
38
0
1
Order By: Relevance
“…Migrant workers, defined by International Labour Organization (ILO) [ 1 ] as “international migrant individuals of working age and older who are either employed or unemployed in their current country of residence” (p. ix), continue to be disproportionally affected by the COVID-19 pandemic [ 2 , 3 , 4 , 5 ]. Accounting for 4.7% of the total global workforce, two-thirds of migrant workers reside in high-income countries [ 1 , 6 ], and are often employed in essential sectors, where physical distancing can be difficult and access to protective equipment limited [ 7 , 8 ], resulting in increased potential exposure to COVID-19 [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Migrant workers, defined by International Labour Organization (ILO) [ 1 ] as “international migrant individuals of working age and older who are either employed or unemployed in their current country of residence” (p. ix), continue to be disproportionally affected by the COVID-19 pandemic [ 2 , 3 , 4 , 5 ]. Accounting for 4.7% of the total global workforce, two-thirds of migrant workers reside in high-income countries [ 1 , 6 ], and are often employed in essential sectors, where physical distancing can be difficult and access to protective equipment limited [ 7 , 8 ], resulting in increased potential exposure to COVID-19 [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, migrants were made to live in perilous conditions and subjected to unkind (working) conditions such as unscrupulous working hours, sometimes exacerbated, compared to the pre-COVID-19 era [ 33 ]. For instance, in Canada, when the COVID-19 pandemic was declared in March 2020, temporary migrant agricultural workers were put under extreme pressure to avoid any disruptions in the food supply chain, which increased work demands leading to multiple reports of abuse [ 34 ]. The Canadian example illustrates how the COVID-19 pandemic has increased the risk of labour rights violations and vulnerability to exploitation for migrant, especially migrant workers [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of other studies also found that farmers experienced many challenges due to the COVID-19 pandemic and did not get optimal support from the government (Nchanjia & Lutomia, 2021;Wegerif, 2021). Five studies (Bossenbroek & Ftouhi, 2021;Jaacks et al, 2021;Kulkarni et al, 2021;Landry et al, 2021;Lusk & Chandra, 2021) described about farmers on their social life from the production process (inputs, harvest and sell), accessing incentives, finding workers and lower income with high risk of disease. All study highlighted the farmers' difficulties in cultivating the land to selling the crops.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic induced lockdown further exposed these vulnerabilities (Kulkarni et al, 2021), The barriers faced were difficulty in harvest, sell the crop, decrease in income and dietary diversity (Jaacks et al, 2021), Structural low wages and new challenges to finding work. Difficulties in benefitting from governmental support programs (Bossenbroek & Ftouhi, 2021), toward lower incomes, greater job insecurity, and more perilous immigration and legal status than the general population, which suggest additional relative financial risks resulting from the burden of medical costs or lost time away from work (Lusk & Chandra, 2021), Substandard living conditions and the spread of the SARS-CoV-2 virus, Barriers to healthcare access, and Barriers to exercising labour rights (Landry et al, 2021).…”
Section: Impact Of Covid-19 To Social Life Farmersmentioning
confidence: 99%
See 1 more Smart Citation